2018
DOI: 10.3855/jidc.8261
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of toxin genes in Staphylococcus pseudintermedius from diseased dogs and other domestic and wild species

Abstract: Introduction: Staphylococcus pseudintermedius is coagulase-positive species of the Staphylococcus intermedius group. It is an opportunistic pathogen that can cause infection in various parts of the body and has a zoonotic potential. Although studies on the pathogenicity and epidemiology of S. pseudintermedius are limited, it is known that this bacterium has several virulence factors, including toxins. These toxins can be classified into three main groups: pyrogenic toxins with superantigenic properties such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Staphylococcus pseudintermediu s is a coagulase-positive species of staphylococci, commonly colonizing the skin and mucous membranes of animals, most often dogs and cats (Bardiau et al 2013 ; Pitchenin et al 2017 ; Chrobak-Chmiel et al 2018 ). It has also been proven that these bacteria are transmitted to humans in contact with animals (Phumthanakorn et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus pseudintermediu s is a coagulase-positive species of staphylococci, commonly colonizing the skin and mucous membranes of animals, most often dogs and cats (Bardiau et al 2013 ; Pitchenin et al 2017 ; Chrobak-Chmiel et al 2018 ). It has also been proven that these bacteria are transmitted to humans in contact with animals (Phumthanakorn et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The production of many enzymes, including coagulase, and the ability to form biofilms determine the multiplication of bacteria and, consequently, the development of infection. It has been shown that some strains can also produce toxins (Garbacz et al 2013 ; Pitchenin et al 2017 ). The presence of these characteristics in strains isolated from human clinical material indicates a risk that should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…In a later study (G omez-Sanz et al 2013), it was shown that all isolates of MSSP (n ¼ 16) also carried lukS/F-I. The Luk-I gene was detected in 29% isolates of S. pseudintermedius obtained from diseased dogs in Lithuania (Ruzauskas et al 2016) and in more than 90% isolates of clinical samples from domestic animals in Brazil (Pitchenin et al 2018).…”
Section: Staphylococcus Intermedius Groupmentioning
confidence: 93%
“…SIET probably has a role in canine pyoderma and chronic otitis (Yoon et al 2010;Youn et al 2011;Bardiau et al 2013;Ruzauskas et al 2016). Almost all the isolates from otitis and dermatitis in domestic animals included in a recent study (Pitchenin et al 2018) produced SIET toxin and 24% of isolates produced EXI exfoliative toxin. The possibility that SIET-producing S. pseudintermedius can cause ophthalmic disease has also been suggested (Kang et al 2014).…”
Section: Staphylococcus Intermedius Groupmentioning
confidence: 98%
See 1 more Smart Citation